1999
DOI: 10.1302/0301-620x.81b1.0810163
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine levels in synovial fluid from hips with well-functioning or loose prostheses

Abstract: We analysed synovial fluid from 88 hips, 38 with osteoarthritis and 12 with well-functioning and 38 with loose hip prostheses. The levels of TNF-␣, IL-1ß (71 hips) and IL-6 (45 hips) were measured using the ELISA technique. Joints with well-functioning or loose prostheses had significantly increased levels of TNF-␣ compared with those with osteoarthritis. Hips with aseptic loosening also had higher levels of IL-1ß but not of IL-6 compared with those without an implant. The levels of TNF-␣ and IL-1ß did not dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 33 publications
3
24
0
1
Order By: Relevance
“…The results regarding TNF-α and IL-6 correspond well with the observations of Nivbrant et al (1999).…”
Section: Discussionsupporting
confidence: 89%
“…The results regarding TNF-α and IL-6 correspond well with the observations of Nivbrant et al (1999).…”
Section: Discussionsupporting
confidence: 89%
“…13,22,23 However, the role of pro-inflammatory cytokines in human disease has been less well characterized. Although there are several reports clearly demonstrating elevated levels of tumor necrosis factor alpha (TNF-a) in serum, joint synovial fluid, and periprosthetic tissues of osteolysis patients, [24][25][26][27] others have failed to observe such differences, with TNF-a levels in osteolysis patients being similar or lower than controls, or undetectable. [28][29][30][31][32] These conflicting findings raise the possibility that the involvement of macrophages in osteolysis may not be limited to pro-inflammatory cytokine signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, micromotion alters the cellular response to wear debris by creating a more aggressive membrane around implants (Bechtold et al 1995). Therefore it seems essential to obtain a stable interface sealed off from joint fluid containing wear debris and osteoclast-activating factors (Nivbrant et al 1999). As regards non-cemented arthroplasty, experimental studies have shown promising effects of hydroxyapatite coating (Kraemer et al 1995, Søballe et al 1991, 1993a.…”
mentioning
confidence: 99%